POTENSI PEMBENAH TANAH BIOCHAR DALAM PEMULIHAN SIFAT TANAH TERDEGRADASI DAN PENINGKATAN HASIL JAGUNG PADA TYPIC KANHAPLUDULTS LAMPUNG - N. L. Nurida; A. Rachman; Sutono Sutono (Universitas Tribhuwana Tunggadewi, 2012)
At present food crop agriculture in the dry land faces to management problem that does not meet with potential and adaptability. Beside problems on how to reduce soil chemical degradation, the rehabilitation activity to recovery soil characteristics is also a problem Agriculture waste product which difficult to decompose such as coconut husk, rice hull, and stem wood is potential to be used as soil amendment through bio-char by incomplete burning. The aim of this study was to test the effects different agricultural waste products in improving soil physical and chemical quality and production of maize. A field experiment was conducted at Taman Bogo Exp Station, Lampung. A split plot design with three replicatees was employed. Main plot was three soil amendment biochars ( SP50, SP75 and KS50), and as sub plot was: control, and three levels of soil amendment application (2,5; 5,0 and 7,5 t/ha). The results showed that three formulas of soil amendments improved f soil physic and chemical charactristics, while different level of soil amendment only significantly affected porosity of soil water available (PAT). Three formulas of soil amendment also increased yield of maize. The proper dose of soil amendment for three formulas ranged from 5,0 to 7,5 t/ha